2013
DOI: 10.1063/1.4827639
|View full text |Cite
|
Sign up to set email alerts
|

Strain modulated optical properties in BiFeO3 thin films

Abstract: Spectroscopic ellipsometry was used to investigate the strain-dependent optical properties of BiFeO 3 thin films. At room temperature, the compressively strained BiFeO 3 /LaAlO 3 thin films show the largest band gap of about 3.12 eV. It redshifts to 2.75 eV for the tensile strained BiFeO 3 /NdScO 3 thin films. With increasing temperature, observable anomalies in the band gap for all strained thin films near 640 K indicate that antiferromagnetic transition temperature is independent of strain and close to its b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
(38 reference statements)
5
27
1
Order By: Relevance
“…3. Although a strong background signal from STO substrates overwhelms most of the phonon modes161718, the Raman peaks from BFO and CFO can still be clearly detected owing to their smaller band gaps of 2.82 eV1920 and 2.51 eV21, respectively. According to the rhombohedral R 3 c symmetry of BFO, the fingerprint around 162 cm −1 , is assigned as A 1 symmetry mode1922.…”
Section: Resultsmentioning
confidence: 99%
“…3. Although a strong background signal from STO substrates overwhelms most of the phonon modes161718, the Raman peaks from BFO and CFO can still be clearly detected owing to their smaller band gaps of 2.82 eV1920 and 2.51 eV21, respectively. According to the rhombohedral R 3 c symmetry of BFO, the fingerprint around 162 cm −1 , is assigned as A 1 symmetry mode1922.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40] The direct band gap of a T-BFO thin film was extracted by a linear extrapolation of an (α·E) 2 versus E plot to zero. 41 The band gap in a T-BFO thin film is approximately 2.89 ± 0.01 eV, which is significantly smaller than that of T-like BFO on LAO (∼3.12 eV) 42 and larger than that of R-BFO on STO (2.77-2.82 eV). 42,43 Noteworthily, it has been known that the band gap of BFO is almost independent to its strain when it is still keeps the same phase.…”
mentioning
confidence: 99%
“…41 The band gap in a T-BFO thin film is approximately 2.89 ± 0.01 eV, which is significantly smaller than that of T-like BFO on LAO (∼3.12 eV) 42 and larger than that of R-BFO on STO (2.77-2.82 eV). 42,43 Noteworthily, it has been known that the band gap of BFO is almost independent to its strain when it is still keeps the same phase. 43 Therefore, it implies that the observed difference in energy gap is phase-dependent, suggesting that the T-BFO found in this study should be different, the common cases of T-like BFO.…”
mentioning
confidence: 99%
“…Moreover, abnormal properties can be induced by the heterointerface in thin film. Previous studies have shown that the nature of the substrate can influence on crystal phase and optical or PC properties of thin film, like the band gap shift or phase change, which could be used to modify the PC properties of the films [6,[68][69][70][71].…”
Section: Filmsmentioning
confidence: 99%
“…13. The sphere templates can be Pluronic block copolymer P123 ((EO) 20 (PO) 70 (EO) 20 , EO is ethylene oxide and PO is propylene oxide), carbon-sphere, and poly styrene sphere. To increase the connectivity between the spheres and the substrate, the template should be kept at a proper temperature for a while.…”
Section: Filmsmentioning
confidence: 99%